PENGARUH MOBILISASI DINI TERHADAP POST OPERATIVE NAUSEA AND VOMITTING PADA PASIEN POST OPERASI DENGAN GENERAL ANESTESI DI RUMAH SAKIT NGUDI WALUYO WLINGI - Taufan Arif (LPPMK STIKES Widyagama Husada, 2022)
Abstract : Post Operative Nausea and Vommitting is one of the most commonly complained postoperative patients with general anesthesia. Provision of early mobilization will speed up metabolism in the body, and accelerate the expression of residual anesthesia that is released through sweating. Early mobilization is one way to reduce PONV. This research method uses quasy experimental design with pre-post-test research with control group design. Sampling uses the Frederer formula. The number of samples studied amounted to 36 respondents. This study uses the RINVR instrument to measure a patient's PONV, and uses an early SOP for mobilization as a reference in providing interventions. This research was conducted in January-February 2020. The results of the study in the treatment group were given early mobilization interventions showing changes before being given the intervention, the mean value showed 11.61 to 0.00 after being given the intervention, and the p value was 0,000. The results of the study in the control group were given pharmako intervention alone showed a change before being given an intervention the mean value showed 9.61 to 0.83 after being given the intervention and the p value was 0,000. The results of the study the effect of early mobilization on PONV showed a P value of 0.003. Early mobilization causes a smooth circulatory system so that the CVC system that was previously disrupted and excreted residual anesthesia through sweat. Suggestions for further researchers to examine the differences in the duration of early mobilization so as to reduce nausea and vomiting in postoperative patients.